Outcomes of early rhythm control vs. rate control strategies for atrial fibrillation in late elderly patients: a systematic review and meta-analysis - Ahmad, Soban; Ahsan, Muhammad Junaid; Kim, Kathryn M.; Abdul Malik, Mohammad Hamza Bin; Ikram, Sundus; Kim, Michael H. (Frontiers in Cardiovascular Medicine, 2025)
Atrial fibrillation (AF) is highly prevalent in late elderly patients, yet optimal management remains uncertain. While early rhythm control has shown benefits in younger populations, evidence in patients over 75 years is limited, and rate control remains the main treatment strategy. We performed a systematic review and meta-analysis comparing early rhythm vs. rate control in elderly AF patients. Seven retrospective studies with a total of 96,699 patients (27,771 rhythm control; 68,928 rate control) were analyzed. The mean ages were 78.1 and 79.5 years in the rhythm and rate control groups, respectively. Rhythm control was associated with a lower risk of stroke (RR 0.82, p = 0.02) but a higher risk of permanent pacemaker implantation (RR 2.54, p = 0.04). All-cause mortality and cardiovascular mortality were similar between the two groups. Our findings suggest that while early rhythm control may reduce stroke risk in the late elderly, it carries higher device-related risks without a mortality benefit. Treatment goals should be individualized and guided by patient comorbidities, preferences, and overall frailty.